Morpho-anatomical characterization of Moringa oleifera in Benue State, Nigeria - Okpara, Onyinyechi Priscilla; Orkuma, Nomyange (Talenta Publisher, 2025)
Morpho-anatomical investigations are invaluable tools for understanding plant ecological strategies and functional adaptations. This study aimed to evaluate the foliar micro and macro morphological variations in Moringa oleifera accessions in Benue State. Methods: Plant materials were collected from three Local Government Areas (Makurdi, Gboko. and Ushongo) in Benue State Nigeria. Quantitative and qualitative foliar features were evaluated from 50 randomly selected trees comprising four plant stands in each population of accession. Epidermal characters were measured and statistically analysed using SIMINT. Results the macro morphological characters evaluated showed that ADGBK (Gboko) accessions had the longest leaflet length (24.00mm), width (15.33mm) and area (367.20mm2). While, the micro-morphological characters (epidermal cell) in NBMKD (Makurdi) accession had the longest cell length (52.10 µm), cell width (UAMKD = 18.44µm) and cell area (808.59 µm2). The stomatal length (UTUSH = 48.00 µm) and width (LSUSH = 24.03 µm) of accessions from Ushongo were the highest. Percental stomatal index value was notably highest (27%) in WUMKD (Makurdi) accessions. The mean leaf morphological and anatomical characters analysed showed significant difference at (p≤ 0.05). Conclusion: Moringa oleifera accessions evaluated showcased unique foliar morphological variations which were due to tolerance and adaptation strategies by each accession to local environmental conditions.